2014
DOI: 10.4103/0301-4738.120208
|View full text |Cite
|
Sign up to set email alerts
|

Not only pregnancy but also the number of fetuses in the uterus affects intraocular pressure

Abstract: Aim:To investigate whether, intraocular pressure (IOP) is affected when there is a second fetus in the uterus during pregnancy.Materials and Methods:Eighty eyes of 40 twin pregnancies (TwPs), 80 eyes of 40 singleton pregnancies (SiPs) and 80 eyes of 40 non-pregnant females (NoPs) were included in the study.Statistical Analysis:Repeated measurements analysis of variance with two factors, one-way analysis of variance (ANOVA) and theTukey's multiple comparison test were used.Results:The mean IOP (MIOP) values in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
1
14
0
1
Order By: Relevance
“…Saylik and Salik [11] have confirmed that not only pregnancy but also a number of fetuses in the uterus affects IOP.…”
Section: Discussionmentioning
confidence: 81%
“…Saylik and Salik [11] have confirmed that not only pregnancy but also a number of fetuses in the uterus affects IOP.…”
Section: Discussionmentioning
confidence: 81%
“…11,12 Episcleral venous pressure has been reported to decrease in pregnant women could be associated with a decrease in general peripheral vascular resistance during pregnancy and might contribute to a decrease in IOP. 13,14 In our study, the mean IOPs in the second and third trimesters of pregnancy right eye were found to be lower than first trimester by 9.33% and 20.33% respectively & 14.2% and 28.84% left eye. The physiological changes in late pregnancy may reduce corneoscleral rigidity, making the results of applanation tonometry falsely low.…”
mentioning
confidence: 82%
“…Proposed mechanisms underlying the decrease in IOP during pregnancy indicate an association between female hormones and increased outflow. 3,13,14 A marked increase in aqueous outflow facility can be associated with progesterone levels in pregnancy. The decrease in IOP with the use of progesterone or the combination of progesterone and estrogen at pharmacologic doses is also reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations